Corrosion of high purity Mg, AZ91, ZE41 and Mg2Zn0.2Mn in Hank's solution at room temperature - Zainal Abidin, Nor Ishida; Martin, Darren; Atrens, Andrej (Elsevier, 2011)
This work compared the corrosion of typical Mg alloys (AZ91, ZE41 and Mg2Zn0.2Mn) and high purity (HP) Mg in Hank's solution at room temperature and in 3% NaCl saturated with Mg(OH)2. Corrosion was characterised by the evolved hydrogen and the surfaces after immersion. Corrosion in Hank's solution was weakly influenced by microstructure in contrast to corrosion in the 3% NaCl solution. This is attributed to the formation of a more protective surface film in Hank's solution, causing extra resistance between the α-Mg matrix and the second phase. The alloys with substantial Zn contents had a shorter incubation period in Hank's solution. © 2010 Elsevier Ltd.